2008
DOI: 10.2217/14622416.9.9.1251
|View full text |Cite
|
Sign up to set email alerts
|

CYP2C19 and Nongenetic Factors Predict Poor Responsiveness to Clopidogrel Loading dose after Coronary Stent Implantation

Abstract: Prediction of responsiveness after clopidogrel loading dose may substantially be improved by adding CYP2C19*2 genotype to nongenetic risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
130
4
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(147 citation statements)
references
References 41 publications
(40 reference statements)
10
130
4
3
Order By: Relevance
“…Compared with CYP2C19*17, CYP2C19*2 and CYP2C19*3 are well-documented as hypofunctioning alleles in healthy subjects and patients with coronary artery and cerebrovascular diseases. 9,12,[22][23][24] These alleles have also been reported to be significantly associated with subacute stent thrombosis and myocardial infarction following percutaneous coronary intervention. 8,25 This correlation is understood to be a leading cause for increased risk of ischemic complications.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with CYP2C19*17, CYP2C19*2 and CYP2C19*3 are well-documented as hypofunctioning alleles in healthy subjects and patients with coronary artery and cerebrovascular diseases. 9,12,[22][23][24] These alleles have also been reported to be significantly associated with subacute stent thrombosis and myocardial infarction following percutaneous coronary intervention. 8,25 This correlation is understood to be a leading cause for increased risk of ischemic complications.…”
Section: Discussionmentioning
confidence: 99%
“…Among the various genetic variants, the enzymatic activity of the CYP system has played an important role in the pharmacokinetics of various drugs. Geisler et al reported that responsiveness after a clopidogrel LD may be predicted by clinical factors and CYP2C19 genotyping 15) . Compared to clinical factors, the CYP2C19 polymorphism has been found to play an essential role in responsiveness to clopidogrel.…”
Section: Discussionmentioning
confidence: 99%
“…Although non-genetic clinical factors may influence the antiplatelet response to clopidogrel, the hepatic cytochrome P-450 (CYP) 2C19 polymorphism has demonstrated the greatest contribution to the clopidogrel response 15,16) . Because the CYP2C19 variant allele ( 2 or 3) is more frequently identified in the Korean population than in Caucasian cohorts 16,17) , pre-procedural platelet reactivity (PR) and the rate of high post-treatment platelet reactivity (HPPR) may be greater in Korean patients than in Caucasian; however, pre-procedural PR after a 300-mg LD of clopidogrel has not been established in largescale Korean patients treated with scheduled PCI.…”
Section: Introductionmentioning
confidence: 99%
“…Необходимость лабораторно-го мониторинга и индивидуального подхода к антиагре-гантной терапии обсуждается давно. Отдельные авторы представляют свой положительный опыт по примене-нию различных лабораторных методов, в том числе генетического тестирования аллельных вариантов цитохрома CYP2C19, в оценке и прогнозе остаточной реактивности тромбоцитов на фоне лечения антиагре-гантами, а также алгоритмы к индивидуальному подбору режима (вид лекарственного препарата, сочетание пре-паратов, доза) антиагрегантной терапии [12][13][14]. Однако одно из последних масштабных исследований, посвя-щенных лабораторному мониторингу антиагрегантов, ANTARCTIC не подтвердило большую эффективность и безопасность лечения при таком подборе по сравнению со стандартным подходом, который не предполагает какого-либо лабораторного мониторинга и изменения на его основе режима антиагрегантной терапии [15].…”
Section: Discussionunclassified